2014
DOI: 10.1074/jbc.m114.595868
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Bacterial Effector-Postsynaptic Density 95/Disc Large/Zonula Occludens-1 (PDZ) Domain Interactions Demonstrates Shigella OspE Protein Promotes Protein Kinase C Activation via PDLIM Proteins

Abstract: Background: PDZ domains provide specificity in protein-protein interactions in eukaryotic systems. Results: Shigella OspE, which is delivered into human cells during infection, binds PDLIM7 via a PDZ interaction and contributes to activation of PKC. Conclusion: During infection, OspE contributes to activation of PKC through PDZ-mediated binding to PDLIM7. Significance: PDZ interactions likely contribute to pathogenesis of several bacterial pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…Bacteria escape this vacuole into the cytosol of the donor cell (Allaoui et al, 1992;Campbell-Valois et al, 2015;Uchiya et al, 1995;Weddle and Agaisse, 2018b), which enables repeated cycles of intercellular spread through the epithelial monolayer. The forces derived from actin-based motility are necessary for protrusion formation (Monack and Theriot, 2001), whereas other pathogen and host factors, including the type 3 secretion translocon pore proteins IpaB and IpaC and the type 3 effectors OspE1/2, IcsB, and VirA, are required for efficient intercellular spread (Allaoui et al, 1995;Campbell-Valois et al, 2014, 2015Heindl et al, 2010;Kuehl et al, 2014;Ogawa et al, 2003;Page et al, 1999;Schuch et al, 1999;Yi et al, 2014;Yoshida et al, 2006). Understanding the molecular mechanisms by which these proteins contribute to spread will define the parameters necessary for bacterial spread.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria escape this vacuole into the cytosol of the donor cell (Allaoui et al, 1992;Campbell-Valois et al, 2015;Uchiya et al, 1995;Weddle and Agaisse, 2018b), which enables repeated cycles of intercellular spread through the epithelial monolayer. The forces derived from actin-based motility are necessary for protrusion formation (Monack and Theriot, 2001), whereas other pathogen and host factors, including the type 3 secretion translocon pore proteins IpaB and IpaC and the type 3 effectors OspE1/2, IcsB, and VirA, are required for efficient intercellular spread (Allaoui et al, 1995;Campbell-Valois et al, 2014, 2015Heindl et al, 2010;Kuehl et al, 2014;Ogawa et al, 2003;Page et al, 1999;Schuch et al, 1999;Yi et al, 2014;Yoshida et al, 2006). Understanding the molecular mechanisms by which these proteins contribute to spread will define the parameters necessary for bacterial spread.…”
Section: Introductionmentioning
confidence: 99%
“…Since IpaC interacts with the cell-cell adhesion protein β-catenin (Shaikh et al, 2003), a component of these catenin-cadherin networks, we hypothesized that the role of IpaC in disruption of cell-cell tension may depend on its interaction with β-catenin and that IpaC R362 may be required for this interaction. In an orthogonal yeast-based protein-protein interaction assay that has been successfully used in the study of host-pathogen protein interactions (de Groot et al, 2011; Russo et al, 2016; Schmitz et al, 2009; Yi et al, 2014), we observed that IpaC R362W is defective for interaction with β-catenin. β-catenin (bait) was fused to the reovirus scaffold protein µNS, which forms inclusions bodies, and IpaC derivatives (prey) were tagged with mCherry.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria escape this vacuole into the cytosol of the donor cell (Allaoui et al, 1992; Campbell-Valois et al, 2015; Uchiya et al, 1995; Weddle and Agaisse, 2018b), enabling repeated cycles of intercellular spread through the epithelium. Whereas the forces derived from actin-based motility are necessary for protrusion formation (Monack and Theriot, 2001), other pathogen and host factors, including the type 3 secretion translocon pore proteins IpaB and IpaC and the type 3 effectors OspE1/2, IcsB, and VirA, are required for efficient intercellular spread (Allaoui et al, 1995; Campbell-Valois et al, 2015; Campbell-Valois et al, 2014; Heindl et al, 2010; Kuehl et al, 2014; Ogawa et al, 2003; Page et al, 1999; Schuch et al, 1999; Yi et al, 2014; Yoshida et al, 2006). Understanding the molecular mechanisms by which these proteins contribute to spread will define the parameters necessary for bacterial spread.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of EspI/NleA, Golgi targeting is partially mediated by a Postsynaptic Density95/Disc Large/Zonula Occludens-1 (PDZ) domain on its C-terminus 54 . CT105 also possesses a putative PDZ domain 56 , but the relevant residues are not involved in its subcellular localization after ectopic expression in mammalian cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%